Six-month study of the effect of a dentifrice containing zinc citrate and triclosan on plaque, gingival health, and calculus - Svatun, B; Saxton, C A; Rölla, G (Scandinavian journal of dental research, 1990)
In two previous studies gingival health was maintained for at least 12 months by a dentifrice containing zinc citrate and triclosan. The aims of the present study were to determine if a zinc/triclosan dentifrice would stabilize gingival health if a lower concentration of zinc was used and to investigate its effect on the formation of calculus. 101 men and women were given oral hygiene instruction and their teeth were professionally cleaned. Two balanced groups were then formed, based on the prestudy levels of gingival bleeding and calculus. One group used the zinc/triclosan dentifrice for 6 months, while the other used a control. Results were assessed after 3 months and 6 months. Following the oral hygiene instruction, plaque and gingival bleeding were assessed at the end of the 4-wk period preceding the experimental phase, and both had been reduced. This improvement was not maintained by the control group, whereas the test group exhibited significantly lower plaque levels and a higher standard of gingival health throughout the 6 months. After 3 months, levels of calculus in the control group had returned to prestudy levels. At both the 3- and 6-month assessments, significantly less calculus was observed in the test group. The improved plaque control, stabilized gingival health, and reduced calculus formation support the conclusion that a dentifrice containing 0.5% zinc citrate and 0.2% triclosan can contribute to oral care.